Digital Economy and MSMEs’ Revenue: Moderating Role of Internet Literacy - Imam Andrianto Al Muffarriddin; Lalu Ahmad Ramadani; Muhammad Muhajir Aminy (Institut Agama Islam Negeri (IAIN) Bone, 2024)
The research investigates the influence of the digital economy on MSMEs’ revenue growth with internet literacy as the moderating variable. This study employed data from 100 MSMEs through Random Sampling and analysis with SPSS software version 26. The results highlight a significant positive correlation between the digital economy and revenue increase, showcasing its role in expanding product marketing through online platforms like e-commerce and facilitating online payments, thus enhancing business efficiency, customer service, and communication. Moreover, the digital economy streamlines sales data recording and analysis, enabling targeted product innovation to directly boost revenue. Notably, internet literacy moderates this relationship, emphasizing the importance of sharing information and knowledge to maximize the benefits of digital tools like online marketing and e-commerce. This underscores the critical need for accessible and affordable internet infrastructure to support SMEs in leveraging digital technologies effectively. The practical implications suggest fostering internet literacy among SMEs and prioritizing initiatives to enhance internet accessibility can significantly contribute to revenue growth, bolstering their competitiveness and sustainability. Policymakers and stakeholders should thus prioritize efforts to provide necessary support and training programs aimed at empowering SMEs to harness the potential of the digital economy for sustained growth and development.